Electroclinical Features of Epilepsy in Mucopolysaccharidosis III: Outcome Description in a Cohort of 15 Italian Patients - Barone, Rita; Fiumara, Agata; Gulisano, Mariangela; Cirnigliaro, Lara; Cocuzza, Maria Donatella; Guida, Claudia; Pettinato, Fabio; Greco, Filippo; Elia, Maurizio; Rizzo, Renata (Frontiers in Neurology, 2021)
Mucopolysaccharidosis III (Sanfilippo syndromes) types A–D are rare lysosomal storage disorders characterized by heparan sulfate accumulation and neurodegeneration. Patients with MPS III present with developmental stagnation and/or regression, sleep disturbance, and behavioral abnormalities usually in the first years of life. Epilepsy may occur in a proportion of patients during the disease course. However, the progression of epilepsy and EEG changes in MPS III have not been systematically investigated. We report electroclinical features in a cohort of patients with MPS III over a follow-up period ranging from 6.5 to 22 years. Participants include 15 patients (11 females; aged 7–31 years) with MPS III A (n = 7, 47%), MPS III B (n = 5, 34%), MPS III C (n = 2, 13%), and MPS III D (n = 1, 6%). At the time of this study, 8 out of 15 patients (53%) had epilepsy. Epilepsy occurred in patients with advanced disease even in the first decade of life (mean age at onset: 12.1 ± 6.7 years). However, seizure onset may also be associated with abrupt worsening of the neurobehavioral phenotype. The main epilepsy types observed were generalized (four out of eight, 50%), followed by focal (three out of eight, 37%) and combined (two out of eight, 25%) epilepsy and status epilepticus (one out of eight, 12.5%). Seizures were generally controlled by one antiepileptic drug (AED) and most patients (seven out of eight, 87%) were still on therapy after a median follow-up period of 5 years (range: 1–9 years). A total of 66 EEGs were analyzed with a median EEG follow-up duration of 7 years (range: 6 months−14 years). Slowing of the background activity occurred in 7 (46%) patients aged 4–19 years. Epileptiform EEG abnormalities were observed in 10 patients at a mean age of 9.6 ± 2.9 years. EEG epileptiform discharges were not unavoidably linked to epilepsy. Early recognition and careful monitoring of electroclinical features in MPS III is necessary for appropriate care and for the detection of disease progression.